2017
DOI: 10.1111/eea.12587
|View full text |Cite
|
Sign up to set email alerts
|

Bethylids attacking stored‐product pests: an overview

Abstract: Bethylidae is a family belonging to the insect order Hymenoptera and contains about 2 200 described species. Bethylids typically parasitize larvae of Lepidoptera and Coleoptera, including species that are serious pests of stored products. Here, we review the main characteristics of each of the bethylids reported as biological control agent of these pests. The biological characteristics and peculiarities are reported for each species, and the potential for their practical application is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 96 publications
(231 reference statements)
0
10
0
Order By: Relevance
“…While live and dead 4th instars of the tested Tribolium spp. were successfully recognized as hosts by parasitoid females, larvae of O. surinamensis were not, although it had been described as host species in the past (Amante et al 2017b ; Evans 1969 ; Hagstrum and Subramanyam 2009 ). Chemical analysis of crude larval extracts revealed that the CHC profiles of Tribolium spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While live and dead 4th instars of the tested Tribolium spp. were successfully recognized as hosts by parasitoid females, larvae of O. surinamensis were not, although it had been described as host species in the past (Amante et al 2017b ; Evans 1969 ; Hagstrum and Subramanyam 2009 ). Chemical analysis of crude larval extracts revealed that the CHC profiles of Tribolium spp.…”
Section: Discussionmentioning
confidence: 99%
“…The polyphagous, cosmopolitan ectoparasitoid Holepyris sylvanidis (Bréthes 1913) (Hymenoptera: Bethylidae) has been described to parasitize larvae of various beetle taxa (i.e. Cucujidae, Silvanidae, Tenebrionidae) infesting processed plant products (Amante et al 2017b ; Evans 1969 ; Hagstrum and Subramanyam 2009 ). Adults and larvae of these beetles are major pests of stored grain or wheat flour and occur worldwide in warehouses and in the food-processing industry (Hertlein et al 2011 ; Vassilakos et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasitoids attacking stored product pests mainly belong to the hymenopteran families Pteromalidae, Ichneumonidae, Braconidae and Bethylidae [ 9 , 10 , 11 ]. Theocolax elegans (Westwood) (Hymenoptera: Pteromalidae) is a cosmopolitan solitary ectoparasitoid of several stored product pests, including the coleopteran species Rhyzopertha dominica F. (Coleoptera: Bostrychidae), Stegobium paniceum L. (Coleoptera: Anobiidae), Callosobruchus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The insect infestation in cultivation and storage regions cause considerable economic losses to agricultural production worldwide (Amante et al, 2017). Among the most damaging species are Tetranychus urticae (Two-spotted spider) and Sitophilus zeamais (Maize weevil) (Baker et al, 2017).…”
Section: Introductionmentioning
confidence: 99%